2015
DOI: 10.4081/ejh.2015.2462
|View full text |Cite
|
Sign up to set email alerts
|

Muc5ac mucin expression during rat skin development

Abstract: Some mucin genes have been detected during human embryonic and fetal organ development; however, little is known about mucin expression in epidermal development, neither in humans nor in other species. The present research was developed to explore Muc5ac skin expression during pre- and post-natal rat development. Immunohistochemistry (IHC), Western blotting (WB) and RT-PCR were employed. By IHC, Muc5ac protein was found early in embryonic epidermis from day 13 of gestation until seven days after birth when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“… 3 For example, MUC5AC is expressed in rat embryonic epidermis and may play a protective role in embryonic skin prior to birth before the mucus is replaced with hair. 11 MUC4 also exists in the skin of embryos and disappears late in gestation, which is consistent with a protective role for mucin in human embryos. 12 Based on these reports, we speculate that mucins appear in embryonic skin to play protective and defensive roles but that mucin expression in adult skin is restricted to reduce the risk of cancer progression.…”
supporting
confidence: 69%
“… 3 For example, MUC5AC is expressed in rat embryonic epidermis and may play a protective role in embryonic skin prior to birth before the mucus is replaced with hair. 11 MUC4 also exists in the skin of embryos and disappears late in gestation, which is consistent with a protective role for mucin in human embryos. 12 Based on these reports, we speculate that mucins appear in embryonic skin to play protective and defensive roles but that mucin expression in adult skin is restricted to reduce the risk of cancer progression.…”
supporting
confidence: 69%
“… 20 The data from the present study successfully fills in the gap of neurotrophin expression in the testis of a seasonal breeder and suggested that NGF system might be actively involved in the seasonal changes in spermatogensis and testicular activity. As we recently found that spermatogensis and testicular function of the wild ground squirrel re-activated during, instead of after, winter hibernation, 30 it will be interesting to further investigate if NGF system also plays a role in this particular process, when the activity of nervous system reaches the low level, for the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MUC5AC expression is never detected in adult bowel unless early stages of neoplasia develop (51). Also, expression of MUC5AC protein had been observed early in embryonic epidermis from day 13 of gestation until 7 days after birth, when the surface epidermis became negative, and the expression restricts to secreting sebum cells (65). Expression of secretory mucin MUC5AC is deregulated in different disease conditions as reviewed in Table 2.…”
Section: Dysregulation Of Muc5ac In Benign Pathologiesmentioning
confidence: 99%